Construction of hydrophilic N, O-rich carboxylated triazine-covalent organic frameworks for the application in selective simultaneous electrochemical detection - Lin, Xiaogeng; Deng, Yanhua; He, Yasan; Chen, Jianhua; Hu, Shirong (Applied surface science, 2021)
[Display omitted] •Constructed a triazine-COFs with high surface area via a simple method.•Developed a hydrophilic N, O- rich carboxylated triazine-COFs.•Fabricated a novel sensor combining the merits of AuNPs and the designed COFs.•The sensor was highly selective in the simultaneous determination of GA and UA. In this study, we strategically designed a hydrophilic N, O-rich carboxylated triazine- covalent organic frameworks (ACOF-TaTp) for the application in selective simultaneous electrochemical detection of mixed chemical compounds with closing oxidation potentials. The ACOF-TaTp was firstly constructed with high surface area and hydrophilicity by 2,4,6-tris(4-aminophenyl)-1,3,5-triazine and 1,3,5-triformylphloroglucinol followed with carboxylation by sodium chloroacetate. Characterizations demonstrated the high surface area and rich N, O-electron donors of ACOF-TaTp facilitated the high dispersion and immobilization of AuNPs on it via electrostatic interactions. Based on their chemical properties, Gallic acid (GA) and uric acid (UA) were selected as model compounds for the test and the result showed their closing oxidation peaks could be clearly separated by ACOF-TaTp, which could be ascribed to its high surface area and stronger affinity to GA than to UA via H-bonding. The constructed sensor AuNPs@ ACOF-TaTp/GCE exhibited high selectivity and sensitivity in the simultaneous determination of GA and UA with a wide linear response in the range of 1–175 μM for GA and 1–150 μM for UA and detection limit of 0.19 μM and 0.25 μM respectively. This work paves a way for strategical design of functionalized COFs for simultaneous electrochemical sensing.